Diffusion-based approach to deploying wireless sensor networks. (28th October 2010) - Machado, R.; Tekinay, S.; Zhang, W.; Wang, G.
An important objective of Wireless Sensor Networks (WSNs) is to reliably sense data about the environment in which they are deployed. Reliability in WSNs has been widely studied in terms of providing reliable routing protocols for message dissemination and reliability of communication from sink to sensors. In this work, we define a reliability metric by the amount of data sensed by the network. In order to satisfy this reliability constraint, we propose a diffusion-based approach for a deployment pattern for the sensor nodes. We show that this deployment pattern achieves sufficient coverage and connectivity and requires lesser number of sensors than popular regular deployment patterns. We further obtain the bounds on establishing connectivity between nodes in the WSN and extend this analysis for heterogeneous WSNs.